Mindfulness in high-performance athletes (Revista de Investigaciones Universidad del Quindío, 2022)
The sports world has a multidimensional character that requires physical and psychological skills to improve and optimize the performance of athletes, mindfulness is used as an effective alternative in the control of the internal events of a high-performance athlete by paying attention to the present moment through the opening to experiences as an experience in itself.On this article seeks to highlight the importance of a psychological preparation with mindfulness techniques, which arises because the objective of mindfulness is not as such to try to control the thoughts, sensations or feelings of athletes, nor to modify or change them, but allows them to flow freely accepting any thought, feeling, emotion or physiological sensation that may appear spontaneously and in turn teach users to maintain concentration on what they should do in the moment according to what happens without thinking about what was or could have been, and think about their present experience.The benefits that this type of preparation brings and that a coach provides through mindfulness, motivation and timely follow-ups are: mental health, emotional health, physical health, and the increase in sports performance of high-performance athletes.
Keywords: Mindfundles; athletes; high-performance; mindfulness